let f(x) = x^3 + kx^2 + 2x -3

When we devide f(x) with (x+2) th result will be a function (let it be R(x) and a remainder of 1:

Then we could write:

==> f(x)= (x+2) * R(x) + 1

Let us substitute with x= -2:

==> f(-2) = (-2+2)* R(-2) + 1

==> f(-2) = 1.........(1)

But, f(x) = x^3 + kx^2 + 2x -3

Let us sustitute x=-2 in f(x) .

==> f(-2) = -8 + 4k - 4 -3 = 1

==> 4k -15 = 1

==> 4k = 16

**==> k= 4**

**==> f(x) = x^3 + 4x^2 + 2x - 3**

**==> f(x) = (x+2)(x^2 + 2x -2) + 1**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now